2018
DOI: 10.1371/journal.pone.0199830
|View full text |Cite
|
Sign up to set email alerts
|

Economic burden of caregiving for persons with severe mental illness in sub-Saharan Africa: A systematic review

Abstract: BackgroundOver the past two decades, the focus of mental health care has shifted from institutionalisation to community-based programs and short hospital stays. This change means that there is an increased role for caregivers, mostly family members, in managing persons with mental illness. Although there is evidence to support the benefits of deinstitutionalisation of mental health care, there are also indications of substantial burden experienced by caregivers; the evidence of which is limited in sub-Saharan … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
43
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(57 citation statements)
references
References 31 publications
8
43
0
1
Order By: Relevance
“…The direct medical costs associated with BD can be high because of the appreciable use of medical services [66,67,106], often exacerbated by misdiagnosis and frequent psychiatric comorbidities [107]. However, there are few published studies on the costs of BD in LMICs although we are aware that there have been reviews examining the economic burden of caregiving for persons with severe mental illness in sub-Saharan Africa [97,108,109]. The cost of medicines will be a key cost component in LMICs in line with other disease areas [31].…”
Section: Bipolar Disorders (Bd) Including Prevalence and Burden Of Ilmentioning
confidence: 99%
“…The direct medical costs associated with BD can be high because of the appreciable use of medical services [66,67,106], often exacerbated by misdiagnosis and frequent psychiatric comorbidities [107]. However, there are few published studies on the costs of BD in LMICs although we are aware that there have been reviews examining the economic burden of caregiving for persons with severe mental illness in sub-Saharan Africa [97,108,109]. The cost of medicines will be a key cost component in LMICs in line with other disease areas [31].…”
Section: Bipolar Disorders (Bd) Including Prevalence and Burden Of Ilmentioning
confidence: 99%
“…Several factors have been shown to contribute to the decline in functioning among people with bipolar disorder including lack of social support and poor healthseeking behaviour [29,43]. In sub-Sahara Africa, the quality of life of patients with bipolar disorder may be worse given the numerous challenges encountered in the management and support of individuals with mental illness [44,45]. For example, in Uganda, with a population of approximately 40 million people [46], there are less than 30 psychiatrists, meaning that for every 1.3 million people, there is one psychiatrist.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, other studies have also found that financial problems were Figure 2: Categories of primary caregiver burden of the study sample using the BFS according to the patients' employment status. among the highest objective burden experienced by caregivers (Yu et al 2017;Addo et al 2018). Financial difficulties faced by caregivers may be contributed by the caregivers assuming sick family members' responsibilities, the length of time taking up in caregiving, particularly in attending to the ill relatives' behavioural disturbances, and also missed work.…”
Section: Discussionmentioning
confidence: 99%
“…Mitsonis and colleagues (2012) found that among the strong predictors of distress were female sex of caregivers, duration of illness and positive and negative symptomatology. In most developing countries, it is also associated with caregiver economic liability (Addo et al 2018).…”
Section: Introductionmentioning
confidence: 99%